PENGARUH BEBERAPA RASIO KEUANGAN TERHADAP HARGA SAHAM, STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sitanggang, Abdonsius (Jurnal Manajemen dan Bisnis, 2012)
This study aimed to examine the effect of Return on Equities (ROE), Debt to Equity Ratio (DER), the Net Book Value (NBV), Dividend Payout Ratio (DPR), Dividend Growth (GTH), the expected rate of return (KSS) to price stock, and examine what factors are the most dominant influence stock prices companies listed in Indonesia Stock Exchange. The samples were Manufacturing companies listed in Indonesia Stock Exchange in 2004-2006. Models of research and analysis of data using multiple linear regression models. The results are consistent with the hypothesis and is consistent with results of previous studies in which the return of equity (ROE), debt-to-equity ratio (DER), the book value (NBV), the dividend payout ratio (DPR), the growth rate of dividends (GTH), the rate of profit or risk-free profits implied (KSS) is lacking simultaneous significant effect on stock prices companies listed in Indonesia Stock Exchange. ROE, DER, NBV, the House of Representatives, GTH and KSS partially significant effect on the price of separation. The results of stock market price analysis (CLP) has a positive relationship with equity returns (ROE), book value of shares (NBV), the dividend payout ratio (DPR) and the growth rate of dividends (GTH). Instead the market price of the stock (CLP) has a negative relationship with debt to equity ratio (DER) and the risk-free profits or gains implied (KSS). The most dominant factors influence stock prices, companies listed on the Indonesia Stock Exchange is the book value of the stock.